Clandestine Dumpsites and Crime in Mexico City: Revisiting the Broken Windows Theory - Massa, Ricardo (Crime & delinquency, 2025)
This paper revisits the broken windows theory with a particular focus on one sign of social disorder: clandestine dumpsites. To explore whether these are predictors of different types of crimes at a neighborhood level, two classification methods were used. Results suggest that clandestine dumpsites have a high predictive capacity for the crimes of dispossession, property damage, house robbery, vehicle theft, and robbery, and have almost none for environmental crimes or robberies of businesses. It is suggested that clandestine dumpsites should be the object of a comprehensive public policy that, in addition to reducing or eliminating the associated health and environmental risks, seeks to reconstitute the social fabric and motivates the long-term recovery of the public space.